Deskripsi Kemampuan Psikomotorik Mahasiswa Pendidikan Kimia pada Titrasi Asam Basa - Eny Enawaty (Jurnal Ilmiah Ar-Razi, 2020)
The background of this research is the need to know the ability of Chemistry Education students, who would be chemistry teacher in the future, in using laboratory equipments, especially in acid-base titration. This study aims to describe the psychomotor ability of Chemistry Education students in acid-base titration. The research method used is descriptive with the instrument which is observation sheet and interview guide. The analyses result shows that the average psychomotor ability of Chemistry Education students is 82.16%, which is categorized as very well. These skills include assembling titration tools which is categorized well with an average percentage of 76.38%, pouring NaOH solution into the burette which is categorized very well with an average percentage of 81.94%, taking the solution which is going to be analyzed into the Erlenmeyer flask which is categorized well with an average percentage of 77.78%, conducting titration which is categorized very well with the average percentage of 86.11%, observing the volume of titrant and the color of analyte which is categorized as enough with average percentage of 60.41%.